A Systematic Review of Lean–Safety Integration for Preventing Fire and Explosion Hazards in Industrial Systems - Dawaman, Muhamad; Ima Ismara, Ketut; Mujiyono, Mujiyono (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2026)
Fires and explosions in industrial environments pose major risks to personnel, assets, and the environment. Lean thinking, traditionally used to improve operational efficiency by eliminating waste, has increasingly been applied to safety management. This study presents a systematic literature review (SLR) of 50 peer-reviewed articles to synthesise current evidence on how lean principles support fire and explosion hazard prevention in industrial settings. The review followed a structured search and selection process based on PRISMA guidelines using major scientific databases. The synthesis indicates that lean contributes to safety improvement through three main mechanisms: (1) enhancing workplace organisation and process visibility, which reduces hazard accumulation; (2) supporting early identification of risk sources through structured process analysis; and (3) strengthening continuous improvement cultures that sustain safety practices. Rather than acting as standalone solutions, lean approaches are most effective when integrated with formal safety and risk assessment methods such as HAZOP and Six Sigma. This review consolidates dispersed knowledge on lean–safety applications and identifies current research trends and gaps. The findings highlight lean as a complementary strategy for systematic hazard prevention while maintaining operational performance. Future research directions include quantitative validation and integration with digital monitoring technologies.